Socioeconomic Position and Oral Health in Chinese Older Adults: A Life Course Approach - Hong, J.; Watt, R.G.; Tsakos, G.; Heilmann, A. (JDR clinical and translational research, 2025)
Objectives: We investigated associations between socioeconomic position (SEP) across childhood, adulthood, and older age and number of teeth among Chinese older adults. Methods: Data came from 15,136 participants aged 65 to 105 y in the Chinese Longitudinal Healthy Longevity Survey (2018 wave). The outcome was number of teeth. Pathways and sensitive period models were tested simultaneously via structural equation modeling. Ordinal logistic regression assessed the accumulation of risk and social mobility models. Differences were examined across 4 birth cohorts. Results: Adult and older age SEP had direct effects on number of teeth in older age (adulthood, direct β = 0.182, P < 0.001; older age, direct β = 0.093, P = 0.005), supporting the sensitive period model. Childhood SEP had an indirect effect on number of teeth (indirect β = 0.130, P < 0.001) through adult and older age SEP, supporting the pathway/accumulation of risk and social mobility models. Effects of SEP on number of teeth were more pronounced in younger cohorts. Graded associations in the expected directions were found between the number of periods in which participants experienced disadvantaged SEP and number of teeth, as well as social mobility trajectories and number of teeth. Conclusion: Among Chinese older adults, the number of remaining teeth is subject to marked social inequalities. Our findings document the simultaneous applicability of life course models and a widening of oral health inequalities in China across generations. Interventions earlier in child and adult life are needed to address this problem and reduce oral health inequalities. Knowledge Transfer Statement: The findings of this study suggest marked socioeconomic inequalities in oral health among Chinese older adults. These inequalities are generated throughout the life course and appear to have widened across cohorts. This study emphasizes that interventions are needed to address the social determinants of oral health at all life stages.